The statue debate: Ancestors and ‘mnemonic energy’ in Paul and now - Dube, Zorodzai (Hervormde teologiese studies, 2015)
Why do people in South Africa fight over statues – even to the extent of tying themselves to a mere bust? Using insights, especially from Jan Assmann, the study develops the argument that material culture (such as images and statues) provides the social energy that drives the manner in which history is told, that is, historiography; they provide the ‘silent objects’ with the power to control the public discourse and collective identity. Statues encapsulate all we need to know, inversely, concerning public discourse, particularly, concerning issues pertaining to control, power and class. From this perspective, those who vandalise them may be regarded as contesting public discourse identity and historiography. Insights from this discussion provide parallel discussions, especially, in Galatians where Paul contrasts the image of Abraham with that of Moses – choosing Abraham as the public image that best represents the identity complexity, cosmopolitan and heterogeneous nature that characterises the Hellenistic context.